PENGARUH FAKTOR-FAKTOR PENARIK KEPARIWISATAAN WISATAWAN ASAL MALAYSIA TERHADAP KEPUTUSAN BERKUNJUNG KE KOTA PEKANBARU (Survei Pada Wisatawan Asal Malaysia yang Berkunjung ke Kota Pekanbaru) - Mukiroh, .; Setiyorini, Heri Puspito Diyah (THE Journal : Tourism and Hospitality Essentials Journal, 2012)
Pull factors tourists from Malaysia to visit Pekanbaru city in principle intended to be used by the government to develop tourism marketing strategies in increasing the number of tourist arrivals from Malaysia to Pekanbaru. Results of research conducted by using an explanatory survey of origin Malaysian tourist visiting Pekanbaru indicate that a visit to Pekanbaru city decision is influenced by a wide range of variables, availability of services, cultural, political stability and security, as well as the availability tourist attractions. The results of the analysis using 0:07% error level indicates that these five variables, either as a whole or partially, a significant effect on decision to visit.